The poverty-environment thesis: was Brundtland wrong? - Angelsen, A. (1997)
The poverty-environment thesis suggests that the poor are both the agents and victims of environmental degradation. Even though the thesis may have been necessary to avoid a North-South confrontation on environmental issues, its validity can be questioned. It is argued that the coexistence of poverty and environmental disruption could more appropriately be seen as the joint consequence of limited opportunities for some groups, uneven processes of development, an unequal distribution of rights and power, and misguided policies. Higher income in many cases increases the pressure on the environment. This will in particular be the case when investments and purchased inputs are used to increase the capacity to exploit natural resources, and where pollution is related to the use of fossil fuels.